THEMATIC STUDY OF VERSES ON MAYSIR: The Relevance and Qur’anic Solutions to Online Gambling in Family Resilience - Wardi Lute; Mohammad Nawir (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2025)
The rise of online gambling in Indonesia has triggered a financial and moral crisis that poses a massive threat to the resilience of the family institution. Although the government has implemented various cyber regulations, online gambling rates remain high and are causing domestic strife. Previous studies have generally examined this phenomenon in a fragmented manner through the lens of formal law, economic impacts, and the moral degradation of the general public. This study aims to fill this academic gap by integrating a specific interpretation of the Maysir verses into the concept of family resilience in the digital age. Through a library research method based on a qualitative-thematic (maudhu’i) interpretive approach, data were collected from relevant Qur’anic verses and supporting scientific literature. The results indicate that the prohibition on maysir in Surah al-Ma’idah, verses 90–91, holds strong contextual relevance to online gambling due to the similarity of their destructive impacts. As a preventive solution, the Qur’an offers a four-pillar model of domestic resilience encompassing spiritual strengthening, the assurance of halal sustenance, selective social environments, and asset management. This study concludes that Qur’anic values have proven effective as practical-transformative guidelines in fortifying families against digital disruption.